Role of aquaporin-3 in hyperosmolarity-induced apoptosis of rat nucleus pulposus cells in vitro - ZHANG Zetong; FANG Lang; GAN Yibo; LI Pei (Di-san junyi daxue xuebao, 2020)
Objective To investigate the role of aquaporin-3 (AQP-3) in hyperosmolarity-induced apoptosis of cultured rat nucleus pulposus (NP) cells. Methods Rat NP cells were cultured under different osmotic pressures (330 and 550 mOsm/kg), and the proliferation and apoptotic rate of the cells were determined using CCK-8 assay and flow cytometry, respectively. Western blotting and real-time quantitative PCR were used to detect the expression levels of apoptosis-related molecules (Bcl-2, Bax, cleaved caspase 3/caspase 3), and immunocytochemistry, Western blotting and real-time quantitative PCR were used to detect the expression of AQP-3 in the cells. The effect of lentivirus-mediated AQP-3 overexpression on apoptosis of NP cells was investigated after hyperosmolar exposure. Results An osmotic pressure of 550 mOsm/kg, as compared with 330 mOsm/kg, significantly decreased NP cell proliferation, increased the cell apoptotic rate, upregulated the expression of the pro-apoptotic molecules Bax and cleaved caspase 3/caspase 3 (P < 0.05), and down-regulated the expression of the anti-apoptotic molecule Bcl-2 (P < 0.05). The cells with lentivirus-mediated AQP-3 overexpression showed an obviously lowered apoptotic rate following the hyperosmolar exposure and significantly reduced expression of Bax and cleaved caspase 3/caspase 3 (P < 0.05) with an enhanced expression of Bcl-2 (P < 0.05). Conclusion Hyperosmolar exposure significantly promotes apoptosis of NP cells and reduce the expression of AQP-3. AQP-3 overexpression can partly attenuate apoptosis of NP cells following a hyperosmolar exposure.